A cibercultura da intolerância política, ou como a linguagem do ódio desconstrói a cidadania - Bardini, Elvis Dieni (2017)
In spite of the democratic potential of cyberspace in the dissemination of information and in the interaction between the subjects, in equidistant parts of the planet, what is flourishing is a wave of intolerance in which cyber-activism is appropriate and re-signified for the organization and dissemination of undemocratic ideals. The present thesis aims to investigate the political polarization between Right and Left, in cyberspace, in particular on facebook from the 2014 elections. The research had as a sample, commentaries in journalistic subjects on the theme "dictatorship" in the fanpage of the ten politicians with the highest number of followers in the period. From the assumption that positive comments to the period constitute a manifestation of political intolerance, (in view of documentation demonstrating crimes against humanity in the period), elements were identified (and described) to indicate the existence of a "cyberculture of intolerance". A set of discourse characteristics of political intolerance in cyberspace. As a possibility, there are perspectives for the construction and promotion of collective spaces aimed at the development of a citizen's conscience and, consequently, respect for democratic values and respect for the guarantees and rights of individuals.